Self-Assembling Peptide-Based Nanoarchitectonics - Zhao, Luyang; Zou, Qianli; Yan, Xuehai (Bulletin of the Chemical Society of Japan, 2019)
Self-assembly is omnipresent in nature. While natural self-assembly systems are complicated in structure, the simplification of natural systems while maintaining their inherent functionalities has proven to be a highly promising route towards artificial nanoarchitectonics with great potential for application. In this review, we summarize our recent works on self-assembling peptide-based nanoarchitectonics, where peptides with a simple molecular structure can modulate the assembly of various species in a flexible and controllable way and efficiently construct nanoarchitectonics with desired functionalities. Our recent findings regarding the applications of self-assembling peptides in the fields of biomimetic photosystems, oriented microtubes for optical waveguiding, and phototherapy are discussed in detail. In addition, the self-assembly mechanism and the effects of peptides on self-assembly are reviewed. This review is expected to provide an understanding of the role of peptides in the assembly of nanoarchitectonics and guidance towards the future design and application of novel functional peptide-modulated self-assembling materials.